Strategi Manajemen Sarana Dan Prasarana Pendidikan Sebagai Upaya Memenuhi Kepuasan Konsumen Pendidikan Di Madrasah Ibtidaiyah Tawakkal Denpasar - Darmawan, Rizqi Wahyu; Sudarsono, Sudarsono; Wahyudi, Nur (Faidatuna, 2021)
Management of educational facilities and infrastructure has an important role regarding the quality of educational institutions where consumers can feel that the management of educational facilities and infrastructure has met expectations or exceeded expectations. It is also intended to attract as much interest as possible to the community towards MI Tawakkal and maintain the image and quality of MI Tawakkal Denpasar. The focus of this research is: (1) What is the management strategy for educational facilities and infrastructure at MI Tawakkal Denpasar?, (2) How is consumer satisfaction with education about educational facilities and infrastructure at MI Tawakkal Denpasar?. This study aims to: (1) determine the management strategy of educational facilities and infrastructure at MI Denpasar, (2) determine consumer satisfaction with education about educational facilities and infrastructure at MI Tawakkal Denpasar. The method used is a qualitative method, the data collection techniques used are interviews, observation, and documentation. Based on this research, it shows that: 1) The management process of school facilities and infrastructure in improving the quality of educational services at MI Tawakkal Denpasar starts from planning needs through open meetings with internal and external school parties, procurement with funding sources independently or from the government, inventory recording in the school Asset Book, use of facilities and infrastructure that are quite good and not complicated, periodic and routine maintenance, elimination of facilities that are not suitable for use, monitoring and reporting as evaluation material for the coming year, 2) Consumer satisfaction with education regarding the management of educational facilities and infrastructure in MI Tawakkal Denpasar is quite satisfied because it has quite complete facilities and excellent management of infrastructure.